Emergency Stress, Hardiness, Coping Strategies and Burnout in Health Care and Emergency Response Workers During the COVID-19 Pandemic - Vagni, Monia; Maiorano, Tiziana; Giostra, Valeria; Pajardi, Daniela; Bartone, Paul (Frontiers in Psychology, 2022)
Objective: Stress is a growing problem in the general population, but most especially for workers responding to the COVID-19 crisis. The present study examines stress and burnout in health care workers and emergency responders during the third COVID wave in Italy. In addition, we explore the value of psychological hardiness and positive coping strategies as protective factors against the ill-effects of stress. Methods: Over a 5-month period in 2021, surveys were administered across all Italian regions to several groups including health care workers (N=220), emergency responders (firefighters, civil protection, ambulance personnel; N=121), volunteer Italian Red Cross workers (N=328), and a comparison group (N=400) drawn from the general population of Italy. Results: Results showed that among the groups, health care workers had the highest levels of emergency stress, while the Red Cross volunteers had relatively lower stress levels. Hardiness and positive coping levels were highest among Red Cross workers, and lowest in the general population sample. The biggest impact on burnout was seen among health care workers, especially on emotional exhaustion and depersonalization. Multiple regression results showed that hardiness operates as a moderator of the effects of emergency stress on emotional exhaustion and depersonalization aspects of burnout, while problem focused coping and stopping negative thoughts also showed moderating effects. Conclusion: These results suggest that health care workers and emergency responders would benefit from additional training in hardiness and positive coping skills.